Religion at the Frontline: How Religion Influenced the Response of Local Government Officials to the COVID-19 Pandemic. (23rd August 2021) - Adler, Gary J; Ortiz, Selena E; Plutzer, Eric; Mayrl, Damon; Coley, Jonathan S; Sager, Rebecca
Abstract: Frontline officials (such as mayors and commissioners) are responsible for local-level responses to the COVID-19 pandemic across the United States. Their actions and attitudes, either in support of or opposition to public health recommendations, have resulted in widespread variation in local-level pandemic response. Despite evidence that religion significantly impacts the general public's response to the pandemic, the influence of religion on officials' behaviors and attitudes is unknown. Using a unique, two-wave, representative survey of frontline officials, we examine how religion influenced officials' reported personal health behaviors (mask wearing, social distancing) and attitudes toward institutional reopenings. Results show high levels of compliance with public health recommendations, but religious nationalism negatively influences all outcomes. Other religious factors, like affiliation and attendance, vary in their influence and even work differently among officials compared to the general public. Frontline officials are key for understanding how religion influences the pandemic and state action more generally.